Interacting performances theory - O'Donoghue, P. (International Journal of Performance Analysis in Sport, 2009)
Performance profiles can be produced for teams and individual athletes in sport. However, a team or individual sportsperson never plays against themselves. Indeed, the way they play is often influenced by the quality and type of opposition. This paper describes the initial research on Interacting Performances Theory. A series of 6 studies provide evidence supporting the four key parts of the theory: (1) The performance is influenced by the particular opponent, (2) The outcome of a performance is influenced by the quality and the type of opponent, (3) The process of a performance is influenced by the quality and the type of opponent and (4) Different players are influenced by the same opponent types in different ways. Although the theory sees the interaction of two competing performers as essential to understanding the nature of their performances, it also recognises the importance of performance profiles. Indeed, it is proposed that performance profiles are enhanced to include details of how teams and individuals perform against different types of opposition.